The microbiome extends to subepidermal compartments of normal skin - Nakatsuji, Teruaki; Chiang, Hsin-I.; Jiang, Shangi B.; Nagarajan, Harish; Zengler, Karsten; Gallo, Richard L. (Nature communications, 2013)
Commensal microbes on the skin surface influence the behaviour of cells below the epidermis. We hypothesized that bacteria or their products exist below the surface epithelium and thus permit physical interaction between microbes and dermal cells. Here to test this hypothesis, we employed multiple independent detection techniques for bacteria including quantitative PCR, Gram staining, immunofluorescence and in situ hybridization. Bacteria were consistently detectable within the dermis and dermal adipose of normal human skin. Sequencing of DNA from dermis and dermal adipose tissue identified bacterial 16S ribosomal RNA reflective of a diverse and partially distinct microbial community in each skin compartment. These results show the microbiota extends within the dermis, therefore, enabling physical contact between bacteria and various cells below the basement membrane. These observations show that normal commensal bacterial communities directly communicate with the host in a tissue previously thought to be sterile. Microbes living in human skin are known to influence the immune system; however, the deeper layers in which immune cells reside were thought to be largely impervious to bacteria. Nakatsuji et al. show that the skin microbiome extends into the dermis, enabling contact with cells below the basement membrane.